2021
DOI: 10.3390/plants10020370
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Application Date of Fertilizer Containing Silicon and Potassium on the Yield and Technological Quality of Sugar Beet Roots

Abstract: Water shortage and drought are a growing problem in Europe. Therefore, effective methods for limiting its effects are necessary. At the same time, the "field to fork" strategy adopted by the European Commission aims to achieve a significant reduction in the use of plant protection products and fertilizers in the European Union. In an experiment conducted in 2018–2020, the effect of the method of foliar fertilization containing silicon and potassium on the yield and technological quality of sugar beet roots was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Smaller increases were observed in 2019, when the value of the soil moisture was high and there was no drought stress. This confirms the results of previous studies, which prove the effect of field experiments of other authors [44]. Pure sugar yield is determined by the biological yield of sugar, which depends on the yield of roots, sugar content and the content of molasses-forming components.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Smaller increases were observed in 2019, when the value of the soil moisture was high and there was no drought stress. This confirms the results of previous studies, which prove the effect of field experiments of other authors [44]. Pure sugar yield is determined by the biological yield of sugar, which depends on the yield of roots, sugar content and the content of molasses-forming components.…”
Section: Discussionsupporting
confidence: 91%
“…Pure sugar yield is determined by the biological yield of sugar, which depends on the yield of roots, sugar content and the content of molasses-forming components. Root yield has the greatest influence on pure sugar yield [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The diameter and length of beetroots correlate with the wet weight of beetroots. Beetroots weight can be increased by spraying 75 -150 g of silica per ha (Artyszak et al, 2021). Growing media containing goat manure increased root diameter by 27.14% and root length by 25.29%, while planting media containing goat manure and husk charcoal increased root diameter by 32.37% and root length by 31.34 % compared to control only Vertisol soil.…”
Section: Diameter and Length Of Red Beetroots (Mm)mentioning
confidence: 99%
“…The dose of bamboo leaf silica fertilizer at 0.60 ppm still needs to be increased in order to increase the wet weight of red beetroots. Artyszak et al, (2021) reported that spraying 75-150 g of silica per ha was able to increase the wet weight of red beetroots.…”
Section: Weight Of Red Beet Tubers (G)mentioning
confidence: 99%
See 1 more Smart Citation